2023
DOI: 10.56536/ijmres.v13i3.514
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Agility: a key to notch ‘Sustainable Business Performance’ in IT-Enterprises of Pakistan

Shabnam Khan,
Saqib Rehman

Abstract: Entrepreneurial agility is an emerging phenomenon that circumambient over the last two decades. It refers to an individual or organizational capability to anticipate, visualize, and exploit unforeseen entrepreneurial challenges and opportunities existed in market. The study is intended to determine the role of entrepreneurial agility inn creating sustainable business performance among IT-enterprises through the mediation of business model innovation. Additionally, the study also tested the moderation of enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…The results of Hosseini, Alizadeh, and Abedi (2019) revealed that EA was positively and significantly linked with human resources management. According to Khan and Rehman (2023), the degree of EA increases investors' confidence and interest in investing in the enterprise. Thus, we expect EA to influence OP, leading to the study's first hypothesis.…”
Section: Entrepreneurial Agility (Ea) and Organizational Performance ...mentioning
confidence: 99%
“…The results of Hosseini, Alizadeh, and Abedi (2019) revealed that EA was positively and significantly linked with human resources management. According to Khan and Rehman (2023), the degree of EA increases investors' confidence and interest in investing in the enterprise. Thus, we expect EA to influence OP, leading to the study's first hypothesis.…”
Section: Entrepreneurial Agility (Ea) and Organizational Performance ...mentioning
confidence: 99%